The Influence of Career Development, Compensation, and Work Environtment on Employee Performance at PT. Bumi Menara Internusa Cirebon - Gina Lovita Sari; Nabilla Rachma; Dharliana Hardjowikarto; Sunimah Sunimah (Publikasi Indonesia, 2025)
Employee performance is a critical determinant of organizational success, particularly in competitive industries such as marine product processing. However, many companies face challenges related to low employee productivity due to insufficient career development, ineffective compensation, and unsupportive work environments. This study aims to analyze the influence of career development, compensation, and work environment on employee performance at PT. Bumi Menara Internusa Cirebon. Using a quantitative approach, data were collected via questionnaires from 142 employees and analyzed through multiple linear regression to evaluate the effects of independent variables on employee performance. The findings indicate that career development and work environment have significant positive effects on employee performance, while compensation shows a positive but not statistically significant influence. These results suggest that opportunities for growth and a supportive workplace play vital roles in enhancing employee productivity, whereas compensation alone may not be sufficient to drive performance improvements. The study implies that organizations should prioritize career development initiatives and foster conducive work environments to sustain employee engagement and effectiveness. Additionally, policymakers and HR practitioners should consider holistic strategies addressing multiple motivational factors to improve labor productivity. Future research should explore additional variables such as leadership style, motivation, and organizational culture to deepen understanding of employee performance drivers across different sectors.